THE MADINAH CHARTER AS A CULTURE AND CIVILIZATION CONCEPT - Yani, Ahmad (Spektra: Jurnal Ilmu-ilmu Sosial, 2021)
Efforts to build a modern civilized society by upholding human values ​​and justice were pioneered by the Prophet Muhammad long before the UN Universal Declaration of Human Rights in 1948, the French Revolution of 1789 or the birth of the American constitution in 1776. Prof. HAR Gibb in his book Writer Islam states, "Islam is actually more than a religious system, Islam is a complete culture." History has recorded well, any nation that struggles for their survival by facing all obstacles in order to maintain its existence, of course one day it will reach a high level of civilization, will find its own culture. They can give "cultural lessons" to other nations in addition to passing on the culture to the nations after that. The Medina Charter is a document drawn up by the Prophet Muhammad SAW, as a formal agreement in 622 AD between himself and all the important tribes and people in Medina. The Medina Charter is also known as the Medina Constitution. Among the important objectives behind the Medina Charter are the creation of security, happiness and goodness for all human beings (all related segments of society), management of the territory by agreement. Because it contains a number of rules related to tolerance and harmony among the Ummah at a time when the world is filled with group fanaticism.